The Illusion of Urbanization: Impact of Administrative Reform on Communities' Resilience. (January 2021) - Botezat, Alina; David, Mihaela; Incaltarau, Cristian; Nijkamp, Peter
While a large body of literature separately documents urban and rural resilience, little is known about how resilience evolves when communities experience an administrative reform that changes their judicial status from rural to urban. This paper explores the effects of the largest post-communist urbanization waves that took place in Romania in the early 2000s, when more communes were reclassified as towns. Using rich administrative data from 2000 to 2014, we employ a two-way fixed effect difference-in-differences research design to examine the impact of the reform on the resilience capacity of the affected communes. Our results reveal that the administrative reform had an initially positive impact on the physical resilience capacity. While the administrative reform did not have a significant effect on the overall resilience capacity of the newly declared towns, there are important differences across groups. The settlements situated in more developed counties and those with higher income levels were among the main beneficiaries. Negatively affected were mainly the poor communes and those that lack accessibility due to their mountain position and being far from big cities. In policy terms, this clearly emphasizes the need for place-sensitive policies complementing the administrative reform in order to help them escape from their rural uprootedness.